Efficacy of Long-Term Treatment of Autosomal Recessive Hypercholesterolemia With Lomitapide: A Subanalysis of the Pan-European Lomitapide Study - D’Erasmo, Laura; Giammanco, Antonina; Suppressa, Patrizia; Pavanello, Chiara; Iannuzzo, Gabriella; Di Costanzo, Alessia; Tramontano, Daniele; Minicocci, Ilenia; Bini, Simone; Vogt, Anja; Stewards, Kim; Roeters Van Lennep, Jeanine; et al. (Frontiers in Genetics, 2022)
Background and aim: Autosomal Recessive Hypercholesterolemia (ARH) is a rare autosomal recessive disorder of LDL metabolism caused by pathogenic variants in the LDLRAP1 gene. Like homozygous familial hypercholesterolemia, ARH is resistant to conventional LDL-lowering medications and causes a high risk of atherosclerotic cardiovascular diseases (ASCVD) and aortic valve stenosis. Lomitapide is emerging as an efficacious therapy in classical HoFH, but less data is available in ARH. Results: This is a sub-analysis carried out in 9 ARH patients included in the Pan-European Lomitapide Study. Age at starting lomitapide was 46 (IQR 39.0-65.5) years with a median duration of treatment of 31.0 (IQR 14.0-40.5) months. At baseline, 4 (44.4%) patients had hypertension, 1 (11.1%) diabetes mellitus, 2 (22.2%) were active smokers and 5 (55.5%) reported ASCVD. The baseline LDL-C was 257.0 (IQR 165.3-309.2) mg/dl. All patients were on statins plus ezetimibe, 3 were receiving LDL-apheresis (LA), and 1 was receiving also PCSK9i. The addition of lomitapide (mean dose 10 mg) resulted in the achievement of a median on-treatment LDL-C of 101.7 mg/dl (IQR 71.3-138.3, 60.4% reduction from baseline) with a best LDL-C value of 68.0 mg/dl (IQR 43.7-86.7, 73.5% reduction from baseline). During follow-up, one patient stopped both PCSK9i and LA. Recurrence of ASCVD events was reported in one patient. The median on-treatment AST and ALT values were 31.1 (IQR 22.6-48.3) U/L and 31.1 (IQR 27.2-53.8) U/L, respectively. Among 6 ARH patients with available fibroscan examination, liver stiffness values recorded at last visit were within the normal range (median 4.7 KPa; IQR 3.6-5.3 KPa) Conclusion: As well as in classical HoFH, lomitapide has been shown to be effective and safe in the therapy of ARH.